Parental Resilience And Marital Satisfaction Among Mothers Of Children With Thalassemia - Yulifa Indri Destiana; Zaujatul Amna; Syarifah Faradina; Zahrani Zahrani (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2025)
Parents of children with thalassemia are vulnerable to experiencing emotional changes upon receiving their child's diagnosis, especially mothers who often play a more central role in caregiving. These changes can manifest as decreased levels of happiness leading to divorce, or positive changes indicating high levels of happiness and marital satisfaction. An important factor influencing marital satisfaction is parental resilience, which refers to parents' efforts to positively adapt when facing specific challenges in caring for a child with developmental disorders. This study aimed to investigate the relationship between parental resilience and marital satisfaction among parents of thalassemia survivors using a correlational design. A total of 80 mothers with thalassemia survivor children in Aceh were selected using quota sampling technique and participated in filling out the PREQ questionnaire and the EMS scale. The data analysis results showed a correlation coefficient (r)=0.056 and (p)=0.621, indicating no significant relations between parental resilience and marital satisfaction among parents of thalassemia survivors.Abstrak: Orang tua yang memiliki anak dengan thalassemia rentan mengalami perubahan emosional setelah mengetahui hasil diagnosis anak, terutama para ibu yang sering kali memainkan peran yang lebih sentral dalam pengasuhan. Perubahan tersebut berupa menurunnya tingkat kebahagiaan yang berujung pada perceraian, maupun perubahan ke arah positif yang menggambarkan tingginya kebahagiaan dan kepuasan dalam pernikahan (marital satisfaction). Faktor penting yang memengaruhi munculnya kepuasan dalam pernikahan adalah ketahanan orang tua (parental resilience), yaitu upaya orang tua dalam beradaptasi secara positif ketika menghadapi situasi tertentu dalam merawat anak dengan gangguan perkembangan. Penelitian ini bertujuan untuk mengetahui hubungan antara parental resilience dengan marital satisfaction pada orang tua yang memiliki anak penyintas thalassemia menggunakan desain korelasional. Sebanyak 80 ibu yang memiliki anak penyintas thalassemia di Aceh dipilih menggunakan teknik quota sampling dan berpartisipasi dalam pengisian kuesioner PREQ dan skala EMS. Hasil analisis data menunjukkan nilai (r) = 0.056 dan (p) = 0.621, artinya tidak terdapat hubungan antara parental resilience dengan marital satisfaction pada orang tua yang memiliki anak penyintas thalassemia.